Spasticity and Dystonia are Underidentified in Young Children at High Risk for Cerebral Palsy. (February 2022) - Miao, Hanyang; Mathur, Amit M.; Aravamuthan, Bhooma R.
Background: Early spasticity and dystonia identification in cerebral palsy is critical for guiding diagnostic workup and prompting targeted treatment early when it is most efficacious. However, differentiating spasticity from dystonia is difficult in young children with cerebral palsy. Methods: We sought to determine spasticity and dystonia underidentification rates in children at high risk for cerebral palsy (following neonatal hypoxic-ischemic encephalopathy) by assessing how often child neurologists identified hypertonia alone versus specifying the hypertonia type as spasticity and/or dystonia by age 5 years. Results: Of 168 children, 63 developed cerebral palsy and hypertonia but only 19 (30%) had their hypertonia type specified as spasticity and/or dystonia by age 5 years. Conclusions: Child neurologists did not specify the type of hypertonia in a majority of children at high risk of cerebral palsy. Because early tone identification critically guides diagnostic workup and treatment of cerebral palsy, these results highlight an important gap in current cerebral palsy care.